Corporate social responsibility Xstrata Tintaya - Pinto Herrera, Honorio Sabino (2015)
The work deals with the Business Social Responsibility (BSR) Xstrata Tintaya (XT). First the BSR concept is defined, then develops what the mining company XT done about counting the contributions of the Tintaya Foundation and the Tintaya Civil Association. Some critical comments on practices by CSR XT in the Tintaya mine since 2006 and recently (2012) in Antapaccay are presented.